ANTI-TUMOR ACTIVITY OF FOUR AYURVEDIC HERBS IN DALTON LYMPHOMA ASCITES BEARING MICE AND THEIR SHORT-TERM IN VITRO CYTOTOXICITY ON DLA- CELL-LINE. - Adhvaryu, Meghna R.; Reddy, Narshimha; Parabia, Minoo H. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The anti-tumor activity and chemopreventive potential of four Ayurvedic herbs viz. Curcuma longa L., Ocimum sanctum L., Tinospora cordifolia (Wild) Miers ex Hook.f & Thomas and Zizyphus mauritiana Lam. were evaluated using Dalton Lymphoma ascites (DLA) tumor model in Swiss Albino mice. The outcome was assessed using survival time, peritoneal ascitic fluid (Tumor volume) and hematological indices as parameters. Animals were divided into five groups (n = 6) viz. one DLA control and four Herb + DLA treated groups. All the four herb + DLA groups were pre-treated with respective herbs for 7 days and hematological indices were measured for entire five groups. On day-8 animals were inoculated with 1x106 DLA cells i.p., and Herb + DLA groups were continued with oral herbal treatment for 21-days. Hematological parameters and tumor volume were assessed to find the effects of herbs. Short term in vitro cytotoxicity was determined by Trypan Blue exclusion method and LDH leakage assay using different concentrations of herbal extracts and 5-FU as a positive control and IC50 for each herbal extract and 5-FU were determined. Oral administration of crude herb increased the survival time and decreased the peritoneal ascitic fluid content significantly. Hb, RBCs and total WBC which were altered by DLA inoculation were restored significantly by all the herbs except O. sanctum. All the four herbs showed in vitro cytotoxic activity against DLA cell-line. Moreover inter group comparison of all the four herbs for anti-tumor activity showed efficacy in the following order- T. cordifolia > Z. mauritiana ≥ C. longa > O. sanctum respectively.